Assessing the impact of climate on mackerel (Scomber japonicus) quality during vehicle transportation: A transportation modeling approach - Seul‐Ki Park; Su‐Jeong Lee; Sung‐Hwan Eom; Kyung Tae Kim; Young‐Sun Lee; Eun‐Song Kim; Sung Bum Son; Won Je Jang; Kee‐Jai Park; Eun‐Woo Lee (Food Frontiers)
Abstract This study investigates the impact of environmental factors on the quality changes of mackerel (Scomber japonicus), a globally significant fish species valued for its high nutritional content, especially its unsaturated fatty acids and proteins. In South Korea, marine products like mackerel undergo auction, sorting, packaging, and transportation. Assessing the fish freshness and quality during these processes, before it reaches consumers, is crucial. This research aimed to track the changes in mackerel quality indicators after the auction and correlate them with the environmental factors affecting transportation. Using a transportation model established for both summer and winter, mackerel samples were categorized by their weight (200 and 300 g). Results show poorer quality indicators in summer compared to winter, particularly in the 200 g group. Microbiological indicators such as the total viable count (0.923) and total coliforms (0.958) were most strongly correlated with the season, whereas the lipid oxidation indicators acid value (0.627) and peroxide value (0.536) were moderately correlated with the season. Interestingly, the wider standard deviation distribution observed in summer suggests that individual mackerel characteristics may influence the degree of quality changes. These findings offer insights into mackerel quality fluctuations during auction and transportation, aiding in future efforts to maintain seafood quality amidst climate change.